How the carnivorous waterwheel plant (Aldrovanda vesiculosa) snaps - Westermeier, Anna S; Sachse, Renate; Poppinga, Simon; Vögele, Philipp; Adamec, Lubomir; Speck, Thomas; Bischoff, Manfred (Proceedings. Biological sciences, 2018)
The fast motion of the snap-traps of the terrestrial Venus flytrap (Dionaea muscipula) have been intensively studied, in contrast to the tenfold faster underwater snap-traps of its phylogenetic sister, the waterwheel plant (Aldrovanda vesiculosa). Based on biomechanical and functional-morphological analyses and on a reverse biomimetic approach via mechanical modelling and computer simulations, we identify a combination of hydraulic turgor change and the release of prestress stored in the trap as essential for actuation. Our study is the first to identify and analyse in detail the motion principle of Aldrovanda, which not only leads to a deepened understanding of fast plant movements in general, but also contributes to the question of how snap-traps may have evolved and also allows for the development of novel biomimetic compliant mechanisms.
Keywords: Plant Leaves; Motion; mechanical modelling; reverse biomimetics; Computer Simulation; Carnivory; Models, Biological; Aldrovanda; listy rostlin; masožravci; pohyb těles; počítačová simulace; plant movement; biologické modely; Biomimetics; biomimetika; biomechanika; Biomechanical Phenomena; Droseraceae; Dionaea; finite-element model